2021
DOI: 10.12659/msm.929303
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Influenza Viruses and Viruses Causing Influenza-Like Illness in Children Under 14 Years Old in the 2018-2019 Epidemic Season in Poland

Abstract: Background This study aimed to investigate the epidemiology of influenza viruses and viruses that caused influenza-like disease in children under 14 years of age in the 2018–2019 epidemic season in Poland, and to identify the public health lessons that can be learned. Material/Methods Nose and throat swabs were used to obtain samples. The samples were analyzed in the National Influenza Center, Department of Influenza Research at the National Institute of Public Health-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The reduction in MPP may be affected by the epidemic year to some extent, but we still believe that it was mainly due to the mitigation measures that rates of MPP were so drastically reduced. In addition, IV is a common pathogen of CAP in children in the winter season, and studies have shown that IV also easily causes outbreaks on school campuses and in kindergartens [ 10 , 11 ]. The mitigation measures were beneficial to restrain the spread of MP and IV in the first place.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in MPP may be affected by the epidemic year to some extent, but we still believe that it was mainly due to the mitigation measures that rates of MPP were so drastically reduced. In addition, IV is a common pathogen of CAP in children in the winter season, and studies have shown that IV also easily causes outbreaks on school campuses and in kindergartens [ 10 , 11 ]. The mitigation measures were beneficial to restrain the spread of MP and IV in the first place.…”
Section: Discussionmentioning
confidence: 99%
“…Similar tendencies can be noticed both in other European countries, as well as in the rest of the world [ 13 ]. In the season 2019/2020, activity of influenza A/H3N2/ and B were increased in relation to the influenza season 2018/2019 [ 14 ]. The highest number of infections with both influenza viruses and influenza-like viruses was recorded among the youngest children aged 0–4 years.…”
Section: Discussionmentioning
confidence: 99%
“…The highest number of infections with both influenza viruses and influenza-like viruses was recorded among the youngest children aged 0–4 years. [ 14 ]. This confirms that younger age is associated with a less mature immune system and greater vulnerability to viruses.…”
Section: Discussionmentioning
confidence: 99%